The Feasibility of Natural Ventilation in Radioactive Waste Repository Using Rock Cavern Disposal Method - 김진; 권상기; Jin Kim; Sang-Ki Kwon (Journal of nuclear fuel cycle and waste technology (Online), 2005)
자연환기는 처분장의 작업 환경 및 위생, 부유 방사성 핵종의 노출 등과 같은 안전문제에 있어 자연환기 자체만으로는 기계적 강제 환기에 비해서 덜 효과적이지만 처분장 내의 수분제거, 작업 환경 조성과 관련하여 라돈 (Rn) 가스의 희석과 같은 향후 처분장의 장기적 환경을 위해서는 중요한 역할을 할 수 있고, 환풍기와 같은 환기 설비를 이용해야하는 기계환기에 비해 경제적으로 매우 효과적 일수 있다. 본 논문에서는 지하 처분장의 건설 및 운영 기간동안 자연환경 조건에 따라 처분장에 스스로 생기는 자연 환기의 타당성에 대하여 기술하였다. 자연 동굴을 통한 자연환기 유사에 의해 밝혀진 증거들과, 수직갱을 갖는 산악 도로터널에서의 자연 환기 측정, 그리고 주어진 자연환기 압력에 의한 공기 발생량 계산 등을 통해서 자연 환기는 한국형 지하 방사성 폐기물 처분장에 잠재적으로 매우 유익함을 알 수 있다. 효과적으로 유도된 자연 환기는 방사성 폐기물 처분장 내에 발생하는 열과 습도, 그리고 라돈 가스를 제어하기에 경제적으로 좋은 방법이 될 수 있다. 자연환기를 통해 처분장의 전반적 열적 특성은 개선될 수 있고, 수분으로 포화된 공기는 효과적으로 건조되고 그 건조상태 유지 기간은 확장 될 수 있을 것이다. Natural ventilation in radioactive waste repositories is considered to be less efficient than mechanically forced ventilation for the repository working environment and hygiene & safety of the public at large, for example, controlling the exposure of airborne radioactive particulate matter. It is, however, considered to play an important role and may be fairly efficient for maintaining environmental conditions of the repository over the duration of its lifetime, for example, moisture content and radon (Rn) gas elimination in repository. This paper describes the feasibility of using natural ventilation which can be generated in the repository itself, depending on the conditions of the natural environment during the periods of repository construction and operation. Evidences from natural cave analogues, actual measurements of natural ventilation pressures in mountain traffic tunnels with vertical shafts, and calculations of airflow rates with given natural ventilation pressures indicate possible benefits from passive ventilation for the prospective Korean radioactive waste repository. Natural ventilation may provide engineers with a cost-efficient method for heat and moisture transfer, and radon (Rn) gas elimination in a radioactive waste repository. The overall thermal performance of the repository may be improved. The dry-out period may be extended, and the seepage flux likely would be decreased.